Pemanfaatan Hasil Alam Ubi Kayu Pada Desa Umbulrejo, Kecamatan Ponjong, Kabupaten Gunungkidul - Pratama, Yohanes Mario (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
Kuliah Kerja Nyata at Universitas Atma Jaya Yogyakarta for 79th period in the year of 2021 is running online while still paying attention to several things so that activities can continue to run well. Group 36 in Unit H is assigned KKN in Umbulrejo Village, Ponjong District, Gunungkidul Regency, Yogyakarta Special Region Province. The group collected all data from Umbulrejo Village through secondary data, namely searching through various sources on the internet and filtered to find valid data. In Umbulrejo Village, it was found that there was an abundance of natural cassava products that were still not fully utilized. Group 36 has a work program that provides education about the use of natural cassava products into chips. Processed chips will be packaged attractively and the marketing stages will be carried out through several media. The program is also equipped with the creation of e-books and videos to support the sustainable development of Umbulrejo Village. The hope is that Umbulrejo Village can realize the potential of the village it has to serve as a means of progress and welfare of the residents of Umbulrejo Village.